Service Learning: Mengintegrasikan Tujuan Akademik Dan Pendidikan Karakter Peserta Didik Melalui Pengabdian Kepada Masyarakat - Endah Setyowati; Alviani Permata (Faculty of Cultural Sciences, 2018)
Service learning is a teaching approach that combines academic goals and the character educationthrough community service activities. Teaching strategies through knowledge, experiences, andreﬂections applied in an interdiciplinary course provide opportunities for students to relate knowledgedirectly from the classroom to community problems with their participation as volunteers in a specifedcommunity. Te community which is chosen as a target group was ftted to the lecture materialswhich emphasized on issues of state discrimination against vulnerable groups and impacts of decreasingenvironmental quality on sustainable peace. Te learning outcomes which is set at level of students'awareness of social problems are measured by changes in perceptions of issues faced by target groupsbefore and after students doing a community service through periodic journal reports.